Comparison of the Diagnostic Accuracy of Magnetic Resonance Cholangiopancreatography (MRCP) with Ultrasound and Computed Tomography (CT) in Evaluation of Patients with Obstructive Jaundice (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Obstructive jaundice patients need surgical intervention to overcome the biliary obstruction. For planning these complex interventions, the radiologist has to precisely assess the etiology, location, level, and extent of the disease.Aim: To compare the diagnostic benefit of Magnetic Resonance Cholangiopancreatography (MRCP) with Ultrasound and Computed Tomography (CT) in the evaluation of patients with obstructive jaundice taking histologic tests and anatomical findings after surgical intervention as gold standard.Study Design: This prospective study included 72 patients who were referred to DCIMCH radiology department with clinical features of biliary obstructive disease.Materials and Methods: All patients were evaluated by Ultrasonography followed by Computed tomography (CT) and Magnetic Resonance Cholangiopancreatography (MRCP). The results were read by radiologists blinded to other imaging findings. The characteristic histopathological diagnosis / surgical findings (as applicable) were considered as gold standard.Results: Diagnostic accuracy of MRCP (98%) in the diagnosis of benign and malignant diseases was relatively high (98% and 98%) as compared to CT (82.86% and 91.43% in benign and malignant respectively) and USG (88% and 88%). In the diagnosis of benign diseases, MRCP was 100% sensitive compared to ultrasound (80.77%), which was more sensitive than CT scan (54.55%).In the diagnosis of malignant diseases, MRCP was more sensitive (95.83%) as compared to CT scan (91.67%), which was more sensitive than ultrasonography (79.17%).Conclusion: MRCP is the best imaging investigation in the pre-operative evaluation for obstructive jaundice patients.J Shaheed Suhrawardy Med Coll 2022; 14(1): 32-36